A Review of confessio.ie, or Practical Thoughts on Digital Editing in Classics - Brandenburg, Yannick (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;Online-Ressource)
Abstract: The Hypertext Stack Project (confessio.ie), which digitizes Bieler’s 1950/51 print edition of Patrick of Ireland’s letters, is one of few critical digital editions in classical scholarship. Hence, besides supplying much supporting material such as translations or images of manuscripts, it aims to serve as a model for digitally editing (late) ancient texts. Confessio.ie succeeds at showing that TEI can be applied to classical texts as well, which has been doubted, and paves the way for a more hypertextual understanding of a textual tradition. The project has worked out a by and large suitable layout for a digital edition of a text with a medieval manuscript tradition. However, future editors will need to give deeper thought to matters such as accurately encoding and presenting an apparatus criticus and improving the user friendliness of the interface. Further, because of inaccuracies in the digital apparatus users will want to exploit confessio.ie’s rich resources not instead of, ...
10.18716/ride.a.13.5
Keywords: classics; critical apparatus; medieval latin; critical edition; digitization